Characteristics of non-responders to self-reported questionnaires in a large inflammatory bowel disease cohort study. (November 2015) - Multone, Eléonore; Vader, John-Paul; Mottet, Christian; Schoepfer, Alain; Fournier, Nicolas; Burnand, Bernard; Michetti, Pierre; Pittet, Valérie
Abstract Background. A major threat to the validity of longitudinal cohort studies is non-response to follow-up, which can lead to erroneous conclusions. The objective of this study was to evaluate the profile of non-responders to self-reported questionnaires in the Swiss inflammatory bowel disease (IBD) Cohort. Methods. We used data from adult patients enrolled between November 2006 and June 2011. Responders versus non-responders were compared according to socio-demographic, clinical and psychosocial characteristics. Odds ratio for non-response to initial patient questionnaire (IPQ) compared to 1-year follow-up questionnaire (FPQ) were calculated. Results. A total of 1943 patients received IPQ, in which 331 (17%) did not respond. Factors inversely associated with non-response to IPQ were age >50 and female gender (OR = 0.37; p < 0.001 respectively OR = 0.63; p = 0.003) among Crohn's disease (CD) patients, and disease duration >16 years (OR = 0.48; p = 0.025) among patients with ulcerative colitis (UC). FPQ was sent to 1586 patients who had completed the IPQ; 263 (17%) did not respond. Risk factors of non-response to FPQ were mild depression (OR = 2.17; p = 0.003) for CD, and mild anxiety (OR = 1.83; p = 0.024) for UC. Factors inversely associated with non-response to FPQ were: age >30 years, colonic only disease location, higher education and higher IBD-related quality of life for CD, and age >50 years or having a positive social support for UC. Conclusions. Characteristics of non-responders differed between UC and CD. The risk of non-response to repetitive solicitations (longitudinal versus transversal study) seemed to decrease with age. Assessing non-respondents' characteristics is important to document potential bias in longitudinal studies.